Synthetic Materials that Affect the Extracellular Matrix via Cellular Metabolism and Responses to a Metabolic State - Sthijns, Mireille M.J.P.E.; van Blitterswijk, Clemens A.; LaPointe, Vanessa L.S. (Frontiers in Bioengineering and Biotechnology, 2021)
In regenerative medicine and tissue engineering, many materials are developed to mimic the extracellular matrix (ECM). However, these ECM-mimicking materials do not yet completely recapitulate the diversity and complexity of biological tissue-specific ECM. In this review, an alternative strategy is proposed to generate ECM, namely synthesizing a material that functions as a drug delivery system, releasing molecules that target cellular metabolic pathways and thereby stimulate the local cells to create their own ECM. This is based on the fact that ECM synthesis, modification, composition, signaling, stiffness and degradation are modulated by cellular metabolism. Metabolism can be targeted at different levels, ranging from modulating the availability of substrates or co-factors to regulating the activity of essential transcription factors. Depending on the drug of interest, its characteristics, mechanism of action, cellular target and application, a different drug delivery system should be designed. Metabolic drugs modulating the ECM require cellular uptake for their function, therefore reversible linkers are recommended. Preferably the metabolic modulators are only released when needed, which will be upon a specific metabolic state, a change in ECM stiffness, or ECM remodeling. Therefore, reversible linkers that respond to an environmental stimulus could be incorporated. All in all, a novel strategy is suggested to develop a tissue-specific ECM by generating a synthetic material that releases metabolic molecules modulating the ECM. Various ways to modulate the ECM properties via the metabolism are reviewed and guidelines for the development of these materials are provided.